(untitled) (Fiep Bulletin - online, 2013)
Amid the various deficiencies occurring among students of early childhood education, cerebral palsy is one that most intrigues educators, about the origin and the consequences do not meet well-established standards and are always difficult to measure in one match is against shortcomings in the action of the teacher with the student and in conducting the group, can be crucial to a positive or negative context. Taking into account that each case has peculiar characteristics, understand each of these peculiarities is essential to learn about what the reactions that each individual develops, the experience that is submited. The purpose of this study, is observe the interactions occurring in a inclusion case of a student with cerebral palsy at public school in order to understand their social-didatic interveniences. This applied longitudinal descriptive research is performed by inductive method, created through careful observation, considering a standard that intends to determine some hypotheses to be research. A cerebral palsy also called chronic encephalopathy is a neurological brain problem, that causes mental or physical disabilities and, providing a permanent group of developmental disorders of posture and moviment. A human neuroplasticity allows frames always evolve in a non-linear and often cause surprises in the results, this way is the construction of a phenotype very propitious to help in the difficulties created by the framework will be discussed. Conclude that education can reduce and even eliminate the harmful consequences of cerebral palsy, yet the teaching tools and stackholders should be better equipped and monitored.